Boulding’s Psychic Capital: The Linking of Individual and Collective Identities - William Walter Bostock (Buletin Psikologi, 2021)
The purpose of this article is to establish that Kenneth E. Boulding, an economist whose work also encompassed many other disciplines, provided a valuable insight within the study of psychology. Boulding observed that while in an economic unit there is a store of financial capital which is necessary for continued existence, also in human nature there is a need for a reserve of psychic capital that is vital for the mental health of the individual and society. Psychic capital does this by providing a link consisting of positive feelings shared between the individual and the larger grouping. Boulding proposed that a coherent body of thoughts, memories, and emotions may be shared between individual and collective minds as shared psychic capital. Finally, some present-day examples are given whereby the consequences of a loss of psychic capital have been observed with particular emphasis on collective depression and suicide.